CHILD-FRIENDLY SCHOOLS IN BUILDING GENERATIONS POSITIVE CHARACTER THROUGH CHARACTER TEACHERS - Elvie Maria; Brilliant Handyman Manalu; Lili Suryati; Andriasan Sudarso; Hendra Soewarno (Jurnal Abdisci, 2024)
By having a positive character, a person will feel his presence in the family, work, and community environment. Students who are the next generation of the nation are formed through the learning process from their families and the surrounding environment, including schools and educators with all their facilities. As educators, teachers are individuals who are sued and imitated, and they play an essential role in building the positive character of students. Child-friendly schools are the government's efforts to support the overall development of children to facilitate the achievement of educational goals and emphasize the importance of a conducive and supportive learning environment to build students' character values so that they have a positive character because they have a positive character is an advantage that is reflected in good nature and attitude, the ability to interact well with anyone, having strong morals, empathy, honesty, kindness, discipline, optimism, resilience, and good self-control. In supporting the government's efforts to create child-friendly schools, the Medan Catholic Education Council-Keusukan Agung has equipped teachers at the kindergarten, elementary, and junior high school levels, participated in child-friendly school seminars, with the theme "building a generation with the positive character through teachers with character", so that teachers realize that they must have a positive character. They can build their students with positive character Because a person's character will be formed through the learning process throughout his life, including in the school environment.